An Analytical Study to Ascertain the Safety of Dashmooli Kwath (Syrup) - Dinesh Kumar Verma (International Journal of Pharmaceutical & Biological Archive, 2025)
Introduction: Worldwide, respiratory problems pose a serious threat to public health. Asthma is among one of the most prevalent respiratory conditions. According to WHO estimates, 300 million people worldwide suffer with bronchial asthma at the moment. In India, the prevalence at age six to seven varies between 4 and 32%. According to its signs and symptoms, causation, prognosis, and treatment, Tamaka Shwasa is a disease entity in Ayurveda that is comparable to bronchial asthma in contemporary terminology. The use of bronchodilators, corticosteroids, and anticholinergics, which have long-term adverse effects and dose dependency, are among the modern therapeutic techniques for bronchial asthma. In the present scenario, one of the effective Ayurvedic formulations used for the present study was Dashmooli Kwath (Syrup). Dashmooli kwath (syrup) was prepared as per the Ayurvedic classics indicated in Tamaka Shwasa (Bronchial Asthma). Dashmooli kwath (syrup) reference was taken from the Chakradatta text book chapter Hikka Shwasa and prepared in Nagarjuna Rasayanashala of Post Graduate Institute of Ayurved, Jodhpur. Aims and Objectives: To analyze the organoleptic character, physiochemical parameters and TLC of Dashmooli kwath (syrup) Dashmooli Kwath (syrup). Materials and Methods: Dashmooli Kwath (syrup) formulations was evaluated. Results and Discussion: The analytical values of the formulation were under the normal values, which indicates that the formulation are standardized, safe and effective in the management of Tamaka Shwasa (Bronchial Asthma). Conclusion: On the basis of the present study it was concluded that Dashmooli Kwath (Syrup) was found safe in analytical study which was deployed in the treatment of Tamaka Shwasa in children